Public innovation (2020)
The complexity involved in the solution for public issues requires innovation. Despite the importance, there is little research to translate theories into practice. The aim of this paper is to investigate innovation for public issues through public innovation laboratories (i-Labs). To achieve this, a systematic literature review from documents published since 2004 up to 2019 in Web of Science® was carried out. Data mining software Vantage Point® and Vosviewer® and qualitative analysis software MAXQDA® were used to study 275 articles. Results show the need to deepen in the construction of the public innovation theory through the development of longitudinal studies. The study also found that it is possible to generate public innovation by the integration of; in the laboratory: co-creation, collaborative innovation, experimentation, public-private partnership and citizen participation.